Analisis Pengaruh Kualitas Pelayanan dan Kepercayaan Terhadap Kepuasan Mahasiswa Pada Fakultas Ekonomi MAB Universitas Islam Kalimantan Banjarmasin - Apriya Santi (Jurnal Ilmiah Ekonomi Bisnis, 2020)
Abstract: Evaluation on the service quality and students’ satisfaction can develop positive perceptions. The purposes of this study are to find out and analyze the effect of service quality on students’ satisfaction simultaneously and partially, and analyze the effect of trust on student’s satisfaction With a purposive sampling technique, there are 150 people sampled as respondents. The analysis technique used to test the hypothesis is multiple linear regression. The results showed that service quality has significant effect on students’ satisfaction simultaneously but only tangible and emphaty that have significant effect on student’s satisfaction partially, and trust has no effect on student’s satisfaction in the Economic Faculty of the Islamic University of KalimantanKeywords : Service Quality, Trust, Satisfaction